Roles of MOV10 in Animal RNA Virus Infection - Su, Feng; Liu, Xueming; Jiang, Yunliang (Frontiers in Veterinary Science, 2020)
Animal epidemic diseases caused by RNA viruses are the primary threat to the livestock industry, and understanding the mechanisms of RNA virus clearance from target cells is critical to establish an effective method to reduce economic losses. As an SF-1, ATP-dependent RNA helicase in the UPF1p family, MOV10 participates in the RNA degradation of multiple viruses mediated via miRNA pathways and therefore contributes to a decrease in the replication of RNA viruses. This review primarily focuses on the bioactivity of MOV10, the mechanism of RNA virus removal, and the potential roles of MOV10 in RNA virus clearance. In addition, clues are provided to reduce animal diseases caused by RNA viruses.